Kajian Tingkat Kesadaran Masyarakat Terhadap Konservasi Jenis Burung di Kawasan Hutan Taman Wisata Alam Bipolo, Desa Bipolo, Kecamatan Sulamu, Kabupaten Kupang, Provinsi Nusa Tenggara Timur (NTT) - Chors Bana; Mamie E. Pellondo’u; Fadlan Pramatana (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2023)
The Bipolo Nature Tourism Park area has fauna potential including 53 species of birds and there are protected bird species. Bird diversity in the Bipolo Nature Park area is increasingly threatened by damage to forest area vegetation caused by local communities such as poaching, illegal grazing, fires, illegal logging of trees and opening roads within the area. This study aims to determine the level of public awareness of the conservation of bird species in the Bipolo Nature Park. This research lasted for one month, namely February-March in Bipolo Village, Sulamu District, Kupang Regency, East Nusa Tenggara Province. There were 84 respondents who were obtained using the purposive sampling method and the slovin formula and analyzed using the descriptive method. The results of the study showed that the community's attitude towards the conservation of bird species in TWA Bipolo Forest with a calculation score of 78.56% in the Good category (Agree), Community perceptions of bird species conservation in Bipolo TWA was 67.13% with the Good category (Agree), Participation community towards the conservation of bird species in Bipolo TWA Forest by 79.99% in the Good category (Agree) and community behavior towards Bipolo TWA Forest by 87.75% in the Very Good category (Strongly Agree).